(3GdJgPjH deG GfaQO cd hGMO ef GdbQGA GdSHYI aj GdeTghQ ef GdQhGjGJs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj, J (B444 (3g` s
(3ChdgG (B:s
(3GeG HYO faYfG Gddg hEjGc aEf fjJi bhjJ ai JUfja eG JaQO Hg cd hGMO ef GdbQGA GdSHYI QMege Gddg ef GdGXgGQ hGdGOZGe hGdgeR s
(3BNQgG (B:s
(3bGd GHh YeQh agPG eG JaQO Hg GdbQGA bO PcQJg Ydi MSH eG TQWJg hgPHJ Pdc ai MPa eG dGaGFOI ai PcQg ai GdJaQO HeG bO GONdg HYVg GdeUfajf ajg hGddg JYGdi GYde s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdCdaGX HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3GdbQGAGJ hGdJLhjOs